Robert Knight : reforming editor in Victorian India - Hirschmann, Edwin, 1932- (Oxford : Oxford University Press, 2008)
This is a historical biography of Robert Knight - a pioneering editor and the founder of The Times of India in Bombay and The Statesman in Calcutta. It covers his entire life from 1825-90 and outlines the history of two major newspapers of our times.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Knight, Robert, -- 1826-1890.; Times of India (Firm) -- History; Statesman Ltd. (Firm) -- History; Newspaper editors -- Great Britain -- Biography; Newspaper editors -- India -- Biography; Newspaper publishing -- India -- History -- 19th century; Newspapers -- History -- 19th century; India -- History -- 19th century